Cytotoxicity of Quercetin and Quercetin-3-O-rhamnoside of Etlingera elatior (Jack) R.M.Sm. leaves against HeLa Cervical Cancer Cells - Herni Kusriani,, Anas Subarnas, Ajeng Diantini, Yoppi Iskandar (Journal of Applied Pharmaceutical Science, 2021)
Etlingera elatior traditionally used for therapeutic purposes. Pharmacological activities of this plant have been reported, one of which is cytotoxic activity. This study aims to isolate cytotoxic compounds against HeLa cervical cancer cell lines from an ethanol extract of the E. elatior leaves. The isolation work was conducted by means of column chromatography and determination of the molecular structure was by spectroscopic data analysis. The cytotoxicity was determined by the 3-(4,5-dimethylthiazol-2-yl)-2,5- diphenyltetrazolium bromide (MTT) method. The results of this study were two isolated compounds identified as quercetin and quercetin-3-O-rhamnoside from the ethyl acetate fraction. These two compounds had cytotoxic activity on HeLa cervical cancer cells which was indicated by the inhibition of cell proliferation with IC50 values were 29.49 and 46.67 μg/mL, respectively. In the migration assay, quercetin and quercetin-3-O-rhamnoside inhibited migration of the HeLa cells significantly at 10 μg/mL as compared with the control, in 24 and 48 hr experiments. This study reinforces the previous evidence of the potential of quercetin and quercetin-3-O-rhamnoside as an anticancer drug candidate.
Keywords: Etlingera elatior (Jack) R.M.Sm., HeLa cell, quercetin, quercetin-3-Orhamnoside.